(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In this article, in order to determine the pharmacostimulating effect of various pharmacological drugs (Butasal, Miosta-H, E-selenium) on the animal body, an increase in their body weight, growth and development was carried out on Karakul lambs. The effect on body temperature, respiration rate per minute and heart rate.